Impact of Social Networks on Educational Inclusion: Scientific Perspectives - Gómez Domínguez, Valentina; Navarro Mateu, Diego; Tébar Yébana, Susana; Gómez Domínguez, María Teresa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The present bibliometric study explores the scientific production on the impact of social networks on the perception of support of families of students with special educational needs (SEN). It analyzes 53 papers published between 2013:2024 collected in Web of Science, highlighting an annual growth of 6.5%. The United States leads in publications, and the United Kingdom leads in citations. Tools such as VOSviewer and R identified collaborative networks and thematic trends, highlighting inclusiveness, social participation, and network analysis. The findings highlight opportunities for social networks to strengthen family-school collaboration, although barriers such as technological inequality persist.